Development of Smart Road Line Detectors Based IoT Architecture for Accident Avoidance - mohd zawawi, mohd faiz; Shabani, Hikma (Progress in Engineering Application and Technology, 2021)
The lack of safety equipment on cars is one of the causes of road accidents. As a result, the car is not in the best possible condition. The majority of automobiles lacking safety features are low-cost or basic models. The objective of this study conducted was to see the extent of the effectiveness of road line detectors when placed on vehicles. In addition, study appropriate methods for road line detectors and finally build an affordable line detector for all vehicles. In this project, one method for lane detection are uses which is Bird’s eye view or perspective view. From this method the canny edge detection will be applied to detect the line from the camera capture and it will appear the result by using OpenCV. The result will show and it will send the warning through the buzzer if the car slight right or left.